Effect of KLF17 overexpression on epithelial–mesenchymal transition of gastric cancer cells. Issue 11 (November 2021) - Li, Shaoyi; Li, Yong; Tan, Bibo; An, Zhaojie
Objective: To investigate Krüppel-like factor 17 ( KLF17 ) expression in normal and gastric cancer tissues and cell lines. Methods: Levels of KLF17 mRNA and protein in GES-1 normal gastric mucosal cells, and NCI-N87, SGC-7901, BGC-823 and HGC-27 gastric cancer cells were analysed by quantitative polymerase chain reaction (qPCR) and western blot. Differences in KLF17 expression between gastric cancer and adjacent tissues were analysed by qPCR and immunohistochemistry. Invasion/migration effects of KLF17 overexpression in BGC-823 and HGC-27 cells were analysed by wound-healing and Transwell chamber assays. Changes in expression of KLF17 and epithelial–mesenchymal transition (EMT)-related genes (matrix metalloproteinase [MMP]-9, vimentin and E-cadherin) were analysed in BGC-823 and HGC-27 cells before and after transfection using qPCR and western blot. Transforming growth factor (TGF)-β1, Smad family member (Smad)2/3 and phosphorylated-Smad2/3 levels in BGC-823 and HGC-27 cells were assessed by qPCR and western blot. Results: KLF17 expression was lower in gastric cancer versus adjacent tissues, and in gastric cancer cell lines versus GES-1 normal gastric mucosal cells, and was positively correlated with degree of cancer-cell differentiation. Wound-healing and Transwell assays showed decreased migration and invasion ability of BGC-823 and HGC-27 cells transfected to overexpress KLF17 . KLF17 overexpression was associated with decreased MMP-9 and vimentin in BGC-823 and HGC-27 cancer cells, and increased KLF17 and E-cadherin. KLF17 overexpression also resulted in decreased levels of TGF-β1 and p-Smad2/3 in BGC-823 and HGC-27 cancer cells. Conclusion: KLF17 is poorly expressed in gastric cancer tissues and cell lines. KLF17 overexpression might inhibit EMT via the TGF-β/Smad pathway, thereby reducing gastric cancer cell invasion and migration. Therefore, KLF17 may become a novel target for treating gastric cancer.